A prospective evaluation of a redefined version of the "minimalistic hybrid approach" algorithm for percutaneous coronary chronic total occlusion revascularization. Issue 4 (5th August 2020) - Agostoni, Pierfrancesco; Scott, Benjamin; Budassi, Simone; Verheye, Stefan; Convens, Carl; Vermeersch, Paul; Zivelonghi, Carlo
Abstract: Objectives: Aim of this study is to prospectively assess the feasibility of the "Minimalistic Hybrid Approach" (MHA) algorithm for chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Background: We recently described the MHA, with focus on the classic hybrid strategies (antegrade wire escalation [AWE] or retrograde wire escalation [RWE], antegrade dissection‐re‐entry [ADR] or retrograde dissection‐re‐entry [RDR]), and also on access site (favoring "wrist" approach: radial, ulnar, and distal radial), introducer French size (favoring 6 French catheters) and nonroutine initial use of dual injection. Methods: The MHA was prospectively attempted in 56 consecutive CTO PCI in 54 patients. Technical success was defined as the achievement of TIMI 3 antegrade flow with residual stenosis <30%, procedural success was defined as technical success without in‐hospital major adverse cardiovascular events. Results: Mean Japanese‐CTO (J‐CTO) score was 2.04 ± 0.95(J‐CTO score ≥ 3 in 30.4%). The lesion‐based technical and procedural success were 94.6%(53/56:three failures, two in the same patient) and 91.1%(51/56:three failures, one tamponade requiring pericardiocentesis and one periprocedural infarction), the patient‐based successes were: technical 98.1%(53/54) and procedural 94.4%(51/54). In 34 procedures (60.7%), the approach was single catheter (always trans‐wrist besides one femoral). Out of the 22(39.3%) lesions approached with dual catheters, one was bi‐femoral, the rest was bi‐wrist. In 29 cases (51.8%) AWE represented the successful technique, ADR in 5(8.9%) and retrograde in 19(33.9%); 3(5.4%) were failures. Conclusions: The current study shows that the MHA algorithm is feasible in almost every CTO lesion and it can lead to extremely successful results once applied by operators well acquainted with the wrist approach and with established experience using the full spectrum of the hybrid algorithm techniques.